ROLE OF VITAMIN D IN ETIOPATHOGENESIS AND METABOLIC ABNORMALITIES SEEN IN POLYCYSTIC OVARIAN SYNDROME - SURANKITA SUKUL; JYOTIRMAYEE BAHINIPATI; ASHOK KUMAR DAS (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Polycystic ovarian syndrome (PCOS) is a common cause of ovarian dysfunction in women in reproductive age group. It is now the leading cause of infertility among premenopausal women. PCOS women usually suffer from metabolic disturbances and insulin resistance (IR). Vitamin D has shown a significant role in glucose and insulin metabolism. Correlation studies have been done to examine the role of vitamin D in PCOS. However, still, Vitamin D status in PCOS remains varied. This study is an attempt to find out the association of Vitamin D with etiopathogenesis and metabolic risk factors seen in PCOS. Methods: Hundred subjects (50 PCOS and 50 age-matched normal control) were recruited for the study. Difference in biochemical parameters in PCOS women and normal group was measured, and association of Vitamin D with etiological and biochemical parameters in PCOS was seen. Results: There was a significant (p<0.001) increase in body mass index, serum insulin, fasting blood sugar (FBS), serum cholesterol, triglyceride, and low-density lipoprotein in PCOS. IR was observed in PCOS cases (homeostatic model assessment for β-cell function and IR = 6.40±1.96) compared to the control group (2.43±0.53). Serum 25(OH) Vitamin D3 was significantly decreased in PCOS (9.04±2.60 ng/ml) compared to control group (20.06±3.28 ng/ml). Negative correlation of serum Vitamin D was found with FBS, serum insulin, IR, HI, and serum testosterone. Vitamin D with metabolic parameters also showed a statistically significant negative correlation. Conclusion: Vitamin D deficiency may be a common comorbid manifestation of PCOS. Hence, Vitamin D supplementation may decrease the potential risk of morbidity and mortality associated with PCOS. However, further studies are needed which should include assessment of Vitamin D in women at various stages of PCOS to enhance the temporal order of Vitamin D deficiency in relation to PCOS.